Protocolo de avistamiento de cetáceos en el Mediterráneo - Revuelta Rueda, Luis; Sánchez Ginés, Carlos; Juan Sobrino, Sergio De; Muñoz Ramírez, Soledad; Parra Arjona, Antonio (Revista Complutense de Ciencias Veterinarias, 2007)
Sin resumen